Asas Larangan Melampui Wewenang Pada Penerbitan Keputusan Presiden Republik Indonesia Tahun 1987-1998 - Erliyana, Anna (Pelita Harapan University, 2004)
The policy making power held by President is difficult to control in practice. Discretionary administrative power is apparently a permanent feature of modernÂ governments, including purportedly democratic ones. But many worrie whether the broad discretionary power that resides in Presidents hand will be used arbitrarily. This research tries to find out how broad Presidents discretionary power is already used through the decree of President. Are there of power in President s discretionary power? How to determine which decree of Presidents is abuse of power is the goal of this research.